Gold Nanoparticles: A New Golden Era in Oncology? - Clara Gerosa; Guido Crisponi; Valeria Marina Nurchi; Luca Saba; Rosita Cappai; Flaviana Cau; Gavino Faa; Peter Van Eyken; Mario Scartozzi; Giuseppe Floris; Daniela Fanni (MDPI AG, 2020)
In recent years, the spectrum of possible applications of gold in diagnostics and therapeutic approaches in clinical practice has changed significantly, becoming surprisingly broad. Nowadays, gold-based therapeutic agents are used in the therapy of multiple human diseases, ranging from degenerative to infectious diseases and, in particular, to cancer. At the basis of these performances of gold, there is the development of new gold-based nanoparticles, characterized by a promising risk/benefit ratio that favors their introduction in clinical trials. Gold nanoparticles appear as attractive elements in nanomedicine, a branch of modern clinical medicine, which combines high selectivity in targeting tumor cells and low toxicity. Thanks to these peculiar characteristics, gold nanoparticles appear as the starting point for the development of new gold-based therapeutic strategies in oncology. Here, the new gold-based therapeutic agents developed in recent years are described, with particular emphasis on the possible applications in clinical practice as anticancer agents, with the aim that their application will give rise to a new golden age in oncology and a breakthrough in the fight against cancer.